Quercetin in semen extender improves frozen-thawed spermatozoa quality and in-vivo fertility in crossbred Kamori goats - Batool, Iqra; Fayyaz, Muhammad Hammad; Hameed, Amjad; Andrabi, Syed Murtaza Hassan; Kausar, Rehana; Shahzad, Muhammad; Mubashir, Yasin; Omur, Ali Dogan; Murtaza, Ghulam; Ditta, Allah; Hussain, Tarique (Frontiers in Veterinary Science, 2024)
This study investigated the antioxidant effect of quercetin treated semen on freeze-thawing spermatozoa quality and in-vivo fertility in crossbred Kamori goats. Thirty two ejaculates from four fertile bucks were diluted in Tris based egg yolk extender with varying levels of quercetin (0, 1, 5, 10 and 15 µM) respectively. Qualified semen samples were pooled and frozen in French straws. The results revealed that addition of quercetin in semen extender increased (P < 0.05) freeze-thawed total motility, progressive motility, rapid velocity, average path velocity, straight line velocity, curvilinear velocity and amplitude of lateral head displacement in response to control group respectively. Quercetin supplementation had no effect on beat cross frequency, straightness and linearity (P > 0.05). Quercetin showed significantly higher (P < 0.05) plasma membrane and acrosome integrity and viability (P < 0.05) of spermatozoa in contrast to control group. Quercetin in semen extender significantly increased (P < 0.05) superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX) and total antioxidant capacity (TAC) levels while reduced (P < 0.05) contents of total oxidant status (TOS) and malondialdehyde (MDA) were noticed in contrast to control group respectively. Ultrasound results revealed that 24/30 (80%) goats were found pregnant with 5 µM quercetin-treated semen while control group had 18/30 (60%) animals pregnant. Thus, it concludes that 5 µM quercetin was found efficient, increased antioxidant status, reduced oxidant production and thus improved spermatozoa quality and in-vivo fertility in goats.